Case report: Implantable cardioverter-defibrillator implantation with optimal medical treatment for lethal ventricular arrhythmia caused by recurrent coronary artery spasm due to tyrosine kinase inhibitors - Jin, Jifu; Xia, Guang; Luo, Yu; Cai, Ying; Huang, Ying; Yang, Zhiyun; Yang, Qinghui; Yang, Bing (Frontiers in Cardiovascular Medicine, 2023)
Coronary artery spasm (CAS) may induce lethal ventricular arrhythmia due to severe and prolonged vessel constriction. Tyrosine kinase inhibitors are associated with the occurrence of CAS. Optimal medical treatment is the first-line therapeutic option for the management of CAS, whereas patients who experienced aborted sudden cardiac death (SCD) may benefit from implantable cardioverter-defibrillator (ICD) implantation. We report a case of a 63-year-old Chinese man receiving tyrosine kinase inhibitor treatment for liver cancer who presented with recurrent chest discomfort and syncope with an elevation of high-sensitivity troponin T. Emergent coronary angiography showed sub-total occlusion of the left anterior descending artery without other signs of CAS. Percutaneous transluminal coronary angioplasty with a drug-coated balloon was performed successfully with the guidance of intravascular ultrasound. After 5 months, the patient returned to the emergency room for chest discomfort and another episode of syncope. The electrocardiogram showed ST-segment elevation in the inferior and V5–V6 leads compared to the previous event. Coronary angiography was repeated immediately and showed significant luminal stenosis at the midportion of the right coronary artery (RCA), whereas, after administration of intracoronary nitroglycerine, a remarkable recovery of RCA patency was noticed. A diagnosis of CAS was made, and soon after that, the patient rapidly developed ventricular arrhythmia in the coronary care unit. After successful resuscitation, the patient recovered completely and received long-acting calcium channel blockers as well as nitrates therapy. ICD implantation was performed considering the high risk of recurrence of life-threatening ventricular arrhythmia. During the follow-up period, the patient has been free of angina, syncope, or ventricular arrhythmia, and ICD interrogation showed no ventricular tachycardia or ventricular fibrillation. We first reported the case of a patient with CAS induced by regorafenib treatment complicated with severe atherosclerotic coronary disease who survived from sudden cardiac arrest. ICD implantation is indicated in patients who experienced aborted SCD for the prevention of the next lethal ventricular arrhythmia.